Time-Scales of Inter-Eruptive Volcano Uplift Signals: Three Sisters Volcanic Center, Oregon (United States) - Rodríguez-Molina, Sara; González, Pablo J.; Charco, María; Negredo, Ana M.; Schmidt, David A. (Frontiers in Earth Science, 2021)
A classical inflation-eruption-deflation cycle of a volcano is useful to conceptualize the time-evolving deformation of volcanic systems. Such a model predicts accelerated uplift during pre-eruptive periods, followed by subsidence during the co-eruptive stage. Some volcanoes show puzzling persistent uplift signals with minor or no other geophysical or geochemical variations, which are difficult to interpret. Such temporal behaviors are usually observed in large calderas (e.g., Yellowstone, Long Valley, Campi Flegrei, Rabaul), but less commonly for stratovolcanoes. Volcano deformation needs to be better understood during inter-eruptive stages, to assess its value as a tool for forecasting eruptions and to understand the processes governing the unrest behavior. Here, we analyze inter-eruptive uplift signals at Three Sisters, a complex stratovolcano in Oregon (United States), which in recent decades shows persistent inter-eruptive uplift signals without associated eruptive activity. Using a Bayesian inversion method, we re-assessed the source characteristics (magmatic system geometry and location) and its uncertainties. Furthermore, we evaluate the most recent evolution of the surface deformation signals combining both GPS and InSAR data through a new non-subjective linear regularization inversion procedure to estimate the 26 years-long time-series. Our results constrain the onset of the Three Sisters volcano inflation to be between October 1998 and August 1999. In the absence of new magmatic inputs, we estimate a continuous uplift signal, at diminishing but detectable rates, to last for few decades. The observed uplift decay observed at Three Sisters is consistent with a viscoelastic response of the crust, with viscosity of ∼1018 Pa s around a magmatic source with a pressure change which increases in finite time to a constant value. Finally, we compare Three Sisters volcano time series with historical uplift at different volcanic systems. Proper modeling of scaled inflation time series indicates a unique and well-defined exponential decay in temporal behavior. Such evidence supports that this common temporal evolution of uplift rates could be a potential indicator of a rather reduced set of physical processes behind inter-eruptive uplift signals.